Mucosal Immunization with the Moraxella Catarrhalis Porin M35 Induces Enhanced Bacterial Clearance from the Lung: A Possible Role for Opsonophagocytosis - Easton, Donna; Cripps, Allan W.; Foxwell, Ruth; Kyd, Jennelle M. (Frontiers in Immunology, 2011)
Moraxella catarrhalis is a significant cause of respiratory tract infection against which a vaccine is sought. Several outer membrane proteins are currently under investigation as potential vaccine antigens, including the porin M35. We have previously shown that the third external loop of M35 was immunodominant over the remainder of the protein for antibody produced in mice against the refolded recombinant protein. However, as this loop is predicted to fold inside the porin channel we also predicted that it would not be accessible to these antibodies when M35 is expressed on the surface of the bacteria in its native conformation. This study investigated the functional activity of antibodies against M35 and those specific for the loop 3 region of M35 in vitro and in vivo. Antisera from mice immunized with M35 or the loop 3-deletion, M35loop3–, recombinant proteins were not bactericidal but did have enhanced opsonic activity, whereas antibodies raised against the loop 3 peptide were not opsonising indicating that the immunodominant loop 3 of M35 was not accessible to antibody as we had previously predicted. Mucosal immunization with M35, M35 that had an antigenically altered loop 3 (M35(ID78)) and M35loop3– enhanced the clearance of M. catarrhalis from the lungs of mice challenged with live M. catarrhalis. The in vivo clearance of bacteria in the mice with the M35-derived protein constructs correlated significantly (p<0.001) with the opsonic activity assessed an in vitro opsonophagocytosis assay. This study has demonstrated that the immunodominat B-cell epitope to loop 3 of the M. catarrhalis outer membrane protein M35 is not associated with immune protection and that M35-specific antibodies are not bactericidal but are opsonising. The opsonising activity correlated with in vivo clearance of the bacteria suggesting that opsonising antibody may be a good correlate of immune protection.